2018
DOI: 10.1139/cjz-2017-0252
|View full text |Cite
|
Sign up to set email alerts
|

Experimental setup influences the cardiovascular responses of decapod crustaceans to environmental change

Abstract: The effects of different holding methods on heart rate (HR) changes in the green crab, Carcinus maenas (Linnaeus, 1758), were investigated. Green crabs were held in perforated plastic boxes (with or without a layer of sand) suspended above the bottom of the tank or strapped to a weighted plastic grate. The HR of green crabs classified as unrestrained (plastic box with or without sand) dropped more rapidly compared with restrained (hanging from band, strapped to grate) green crabs. Within 1 h, unrestrained gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…The crustacean cardiovascular system may respond differently to environmental triggers when animals are restrained in an experimental setup [11], which was necessary for present MRI experiments. This may impact the present results and limit their applicability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crustacean cardiovascular system may respond differently to environmental triggers when animals are restrained in an experimental setup [11], which was necessary for present MRI experiments. This may impact the present results and limit their applicability.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that these periodic fluctuations in cardiovascular activity may conserve energy over time [10]. Crustaceans are able to adjust their cardiac output through independently modulating HR and SV [11]. This is evidenced by constant stroke volumes with increasing heart rates above certain, species-specific temperature thresholds [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of continuous recordings in respirometry experiments showed that any initial elevations in oxygen consumption lasted less than 20 min (data not shown). Some authors have also utilized pauses in heart rate as an indicator of reduced stress in crabs (McGaw and Nancollas, 2017). In our study, the mean time of acardia onset in control crabs was 86 min (data not shown), suggesting that crabs settled relatively quickly into chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological responses. Pain activates various physiological responses, such as modifications in heart rate, respiration and/or hormonal levels [ 17 , 73 , 82 , 83 ], and these are generally regarded as stress responses. Stress is a biological response that an animal exhibits to cope with a threat to its homeostasis [ 84 ].…”
Section: Pain Stress and Potential Suffering In Decapod Crustaceamentioning
confidence: 99%